The Effect of Google Classroom in Improving Learning Motivation and Critical Thinking Skills of University Students - Shindy Lestari; Aninditya Sri Nugraheni (STAI Hubbulwathan Duri, 2022)
This research aims to determine the effect of the google classroom platform on educational innovation courses in improving learning motivation and critical thinking skills of PGSD students of Riau University. This study uses a type of quasi-experimental research with its research design is nonequivalent control group design which has an experimental group and a control group. The sampling used in this study is the purposive sampling technique. The results showed that the influence of the google classroom platform on educational innovation courses in improving: 1) Student learning motivation saw simple Pearson correlation test results in a control class of 0.781 and an experimental class of 0.790 with a high category. 2) Critical thinking skills of students viewed the average results of the analysis of the verified Gain test showed a moderate increase in the experimental class of 0.4881 and a control class of 0.4390. This study conducted hypothetical testing of research showing that the influence of google classroom platform on educational innovation courses in improving learning motivation and critical thinking skills of PGSD students of Riau University judging by the results of paired sample t-test in control classes and experimental classes obtained significance (Sig.) of 0.000 0.05 which showed Ho rejection and Ha is accepted.